Frequency of activating mutations in FGFR2 exon 7 in bladder tumors from patients with early-onset and regular-onset disease - Spiegelberg, Christine; Giedl, Josef; Gaisa, Nadine T.; Rogler, Anja; Riener, Marc-Oliver; Filbeck, Thomas; Burger, Maximilian; Ruemmele, Petra; Hartmann, Arndt; Stoehr, Robert (International Journal of Clinical and Experimental Pathology, 2014)
The FGF/FGFR-system plays an important role in embryogenesis, tissue homeostasis and carcinogenesis. Mutational activation of FGFR2 resulting in aberrant FGFR2 signaling activation is known from both hereditary germ line alterations and somatic mutations in various malignancies (e.g. breast, gastric or ovarian cancer). FGFR2 mutations are mainly located within the hinge between Ig-like domains (exon 7), around the 3rd Ig-like domains and within the kinase domain. For bladder cancer only sparse data on FGFR2 mutations are available. Most interestingly a case of early-onset papillary carcinoma of the bladder showing a FGFR2 p.Pro253Arg mutation in exon 7 in a patient with Apert Syndrome was reported recently. To further evaluate the importance of FGFR2 exon 7 alterations in bladder cancer a cohort of 254 bladder tumors (cohort 1: unselected cases: n=139; cohort 2: early-onset bladder cancer cases (age at time of diagnosis<=45 years): n=115) was analyzed. Sections from formalin-fixed, paraffin-embedded bladder tumors were used for DNA isolation. After precise microdissection exon 7 of the FGFR2 gene was analyzed by direct Sanger sequencing. All cases could be analyzed successfully. Mutations in exon 7 of FGFR2 could not be detected in any of the cases. All tumors showed wild type sequence. Our data demonstrate that the recently reported association between early-onset papillary carcinoma of the bladder with germ line FGFR2 p.Pro253Arg mutation could not be found in our cohorts of sporadic bladder tumors. These results indicate that FGFR2 gene mutations might only play a minor role in bladder carcinogenesis.
EVALuna2:6601